PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA WO. FAVORIT DECORATION DI SITUBONDO - Amin, Atssil Revinda Kharisma; Arief, Muhammad Yahya; Ediyanto, Ediyanto (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Marketing is an activity to fulfill needs and desires by influencing consumers to be willing to buy products or use services offered by the company in order to obtain a profit or profit. The need for the right strategy, especially to increase the means in promoting WO. Favorite Decoration in Situbondo Regency. The purpose of this study was to examine and examine the effect of promotion and service quality in determining consumer satisfaction through purchasing decisions as an intervening variable. The population in this study uses the entire consumer WO. Favorite Decoration according to the data that the researcher asked the owner of the research place. The sampling method uses probability sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model – Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that promotion has a significant positive effect on purchasing decisions, service quality has a negative but not significant effect on purchasing decisions, promotions have a significant positive effect on consumer satisfaction, service quality has a significant positive effect on consumer satisfaction, decisions purchases have a significant positive effect on consumer satisfaction. The results of the indirect influence hypothesis show that the promotion variable on consumer satisfaction through purchasing decisions has a significant positive effect, service quality on consumer satisfaction through purchasing decisions has a negative but not significant effect.